Inhibition of Borna disease virus replication by an endogenous bornavirus-like element in the ground squirrel genome - Fujino, Kan; Horie, Masayuki; Honda, Tomoyuki; Merriman, Dana K; Tomonaga, Keizo (Proceedings of the National Academy of Sciences - PNAS, 2014)
Animal genomes contain endogenous viral sequences, such as endogenous retroviruses and retrotransposons. Recently, we and others discovered that nonretroviral viruses also have been endogenized in many vertebrate genomes. Bornaviruses belong to the Mononegavirales and have left endogenous fragments, called "endogenous bornavirus-like elements" (EBLs), in the genomes of many mammals. The striking features of EBLs are that they contain relatively long ORFs which have high sequence homology to the extant bornavirus proteins. Furthermore, some EBLs derived from bornavirus nucleoprotein (EBLNs) have been shown to be transcribed as mRNA and probably are translated into proteins. These features lead us to speculate that EBLs may function as cellular coopted genes. An EBLN element in the genome of the thirteen-lined ground squirrel (Ictidomys tridecemlineatus), itEBLN, encodes an ORF with 77% amino acid sequence identity to the current bornavirus nucleoprotein. In this study, we cloned itEBLN from the ground squirrel genome and investigated its involvement in Borna disease virus (BDV) replication. Interestingly, itEBLN, but not a human EBLN, colocalized with the viral factory in the nucleus and appeared to affect BDV polymerase activity by being incorporated into the viral ribonucleoprotein. Our data show that, as do certain endogenous retroviruses, itEBLN potentially may inhibit infection by related exogenous viruses in vivo.